Public spaces as spaces of politics - da Costa Gomes, Paulo Cesar; Parente Ribeiro, Letícia (Geografares, 2018)
The political activation of public spaces is commonly associated with their extraordinary mobilization by large social movements. On the contrary, a strong political significance is rarely attributed to the everyday and ordinary use of these spaces. Based on a discussion about the strategy of political manifestation known as “occupation” and presenting examples from research carried out in public spaces in the city of Rio de Janeiro, this article proposes a new approach to this opposition, still dominant in academic literature.Keywords: public space; occupy; sociability.